TEACHERS' CREATIVITY IN DEVELOPING LEARNING MEDIA IN EARLY CHILDHOOD EDUCATION INSTITUTIONS IN GUNUNG TOAR - Zulhaini, Zulhaini; Termizi, Termizi; Nahwiyah, Sopiatun (PT Ilmu Inovasi Nusantara, 2023)
Creativity is the power and or human ability to create something. A teacher is required to be creative and innovative, especially teachers who teach at Early Childhood Education (PAUD) institutions. However, there are still problems found in the field such as: Teachers are less creative in developing learning media This study aims to determine the Creativity of Teachers in Developing Learning Media by Utilizing Natural Materials in PAUD Institutions throughout the Gunung Toar District, Kab. Kuantan Singingiwith research methods with data collection techniques is a qualitative method with data collection techniques are questionnaires, observation, interviews and documentation, data analysis techniques using data triangulation, namely data reduction, data presentation and conclusions. The results of research on teacher creativity in developing learning media by utilizing natural materials in PAUD institutions are: a. Using dead banana leaves to stick pictures of animals, b). Using natural materials such as using banana and papaya leaves to form a necklace or bracelet. c). Playing Water, d). Playing with Sand, e) Introducing colors with natural materials. The method used by the teacher in learning the Playing and Telling Methods. This method is applied because children at this age play in the world according to the motto